RISET KEWIRAUSAHAAN SEBAGAI JEMBATAN KESENJANGAN ANTARA TEORI DAN PRAKTIK: PENDEKATAN INTEGRATIF BERBASIS KONTEKS - Mulyana Surya; Yan Noviar Nasution; Heri Iswanto (Economicus : Jurnal Ekonomi dan Manajemen, 2026)
The gap between theory and practice is a classic issue in entrepreneurship studies. Many entrepreneurship theories are developed within a framework of high abstraction and universal generalization, while entrepreneurial practice takes place in dynamic contexts, full of uncertainty, and is influenced by social, cultural, and institutional factors. This article aims to examine the role of entrepreneurship research as a bridging mechanism between theory and real-world practice. The method used is a conceptual review based on recent scientific literature (2015–2025) from reputable international and national journals. The results show that entrepreneurship research serves not only as a producer of theory but also as a co-production arena for knowledge between academics and practitioners. This article contributes theoretically by offering a conceptual framework of entrepreneurship research as an integrative process that balances scientific rigor and practical relevance, as well as methodologically encouraging contextual and reflective research approaches.